Diet quality, excess body weight and cardiometabolic risk factors in adolescents living in São Paulo, Brazil and in the USA: differences and similarities. Issue 13 (10th September 2021) - Pereira, Jaqueline L; Mattei, Josiemer; Isasi, Carmen R; Van Horn, Linda; Carnethon, Mercedes R; Daviglus, Martha L; Perera, Marisa J; Sotres-Alvarez, Daniela; Fisberg, Regina M
Abstract: Objective: To compare diet quality and its association with excess body weight (EBW: overweight/obesity), central adiposity (CA) and CVD risk factors (CVDR) among adolescents from Brazil and USA. Design: Data from two cross-sectional surveys: Health Survey of São Paulo (ISA-Nutrition) and Hispanic Community Health Study/Study of Latino Youth (SOL-Youth). Dietary intake was assessed from 24-h recalls, and diet quality using the Alternate Healthy Eating Index-2010 (AHEI) developed in the USA and the Revised Brazilian Healthy Eating Index (BHEI-R). CVDR was defined as ≥3 of: obesity, elevated blood pressure, dyslipidaemia, high plasma glucose and insulin resistance. Adjusted OR for EBW, CA and CVDR by diet quality were tested using logistic regression. Setting: São Paulo, Brazil; and Chicago, IL; Miami, FL; Bronx, NY; San Diego, CA. Participants: Adolescents (12–16 years) living in São Paulo ( n 189) and USA ( n 787). Results: ISA-Nutrition individuals with EBW ( v . without) had marginally lower (unhealthier) scores for whole grains using BHEI-R and sugary beverages using AHEI. SOL-Youth individuals with EBW had lower scores of nuts/legumes using AHEI, and Na using BHEI-R, but higher scores of whole grains and dairy using BHEI-R. In ISA-Nutrition, BHEI-R was inversely associated with EBW (OR = 0·87; 95 % CI 0·80, 0·95) and CVDR (OR = 0·89; 95 % CI 0·80, 0·98). In SOL-Youth, AHEI was inversely associated with EBW (OR = 0·93; 95 % CI 0·87, 0·99). Conclusions: Dietary improvements should be made by adolescents in both USA and Brazil. Healthier diet quality as measured with the country-specific index was associated with lower odds of EBW in Brazilian and USA-Hispanic/Latino adolescents, and with lower CVDR in Brazilian adolescents.